Membersihkan Jiwa dengan Muhasabah: Kitab Introspeksi untuk Menuai Kesucian Diri - SYAHATAH, Husain Husain (Mitra Pustaka, 2003)
Membersihkan Jiwa dengan Muhasabah: Kitab Introspeksi untuk Menuai Kesucian Diri